The London bookshop affair : a novel of the Cold War - Fein, Louise (William Morrow, 2024)
"A new historical drama from Daughter of the Reich bestselling author Louise Fein, about a London bookshop involved in an espionage network, set against the backdrop of the Cuban Missile Crisis, perfect for fans of Kate Quinn and Pam Jenoff"--